2020
DOI: 10.1080/14756366.2020.1835884
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold hopping and optimisation of 3’,4’-dihydroxyphenyl- containing thienopyrimidinones: synthesis of quinazolinone derivatives as novel allosteric inhibitors of HIV-1 reverse transcriptase-associated ribonuclease H

Abstract: Bioisosteric replacement and scaffold hopping are powerful strategies in drug design useful for rationally modifying a hit compound towards novel lead therapeutic agents. Recently, we reported a series of thienopyrimidinones that compromise dynamics at the p66/p51 HIV-1 reverse transcriptase (RT)-associated Ribonuclease H (RNase H) dimer interface, thereby allosterically interrupting catalysis by altering the active site geometry. Although they exhibited good submicromolar activity, the isosteric replacement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Methods of investigation are shown in Figure 3. Recently, we also reported on the ability of some 3,4-catechol-thienopyrimidinone [30,31] and quinazolinone derivatives [32], originally designed to allosterically inhibit the HIV-1 RT-associated Ribonuclease H (RNase H) function, to hamper LEDGF/p75-dependent IN activity. Interestingly, with regard to thienopyrimidinones, we observed that the 2-(2,3dihydroxyphenyl)-6-methyl-5-propylthieno [2,3-d]pyrimidin-4(3H)-one (5), bearing a 2,3catecol moiety, displayed the best IN inhibitory activity [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods of investigation are shown in Figure 3. Recently, we also reported on the ability of some 3,4-catechol-thienopyrimidinone [30,31] and quinazolinone derivatives [32], originally designed to allosterically inhibit the HIV-1 RT-associated Ribonuclease H (RNase H) function, to hamper LEDGF/p75-dependent IN activity. Interestingly, with regard to thienopyrimidinones, we observed that the 2-(2,3dihydroxyphenyl)-6-methyl-5-propylthieno [2,3-d]pyrimidin-4(3H)-one (5), bearing a 2,3catecol moiety, displayed the best IN inhibitory activity [30].…”
Section: Resultsmentioning
confidence: 99%
“…The previously reported procedure was used for preparation and purification of wild type p66/p51 HIV-1 RT. Enzyme was stored in a 50% glycerol-containing buffer at −20 °C [ 32 , 46 ]. An 18-nt 3′-fluorescein-labeled RNA annealed to a complementary 18-nt 5′-dabsyl-labeled DNA was used to determine IC 50 values, following a previously described procedure [ 47 ].…”
Section: Methodsmentioning
confidence: 99%